CO2 free production of ethylene oxide via liquid phase epoxidation of ethylene using niobium oxide incorporated mesoporous silica material as the catalyst. Issue 3 (10th January 2023) - Maqbool, Muhammad; Akhter, Toheed; Faheem, Muhammad; Nadeem, Sohail; Park, Chan Ho; Mahmood, Asif
Abstract : Ethylene Oxide (EO) is an essential raw material used in various consumer products like different glycol derivatives, ethoxylates, and polymers. Abstract : Ethylene Oxide (EO) is an essential raw material used in various consumer products like different glycol derivatives, ethoxylates, and polymers. We hydrothermally synthesize niobium oxide incorporated with mesoporous silica material (Nb/MSM), an efficient catalyst for CO2 free-ethylene oxide (EO) production via partial oxidation of ethylene. The structural properties of Nb/MSM catalysts were characterized using XRD, TEM, and N2 adsorption–desorption. The catalytic activity of synthesized materials in liquid phase epoxidation (LPE) of ethylene was evaluated in the presence of peracetic acid (PAA) as an oxidant to avoid the production of CO2 and also minimize metal leaching. GC chromatography was used to investigate the successful production of EO, and a peak with a retention time (RT) of 9.01 min served as confirmation. Various reaction parameters viz. temperature, catalyst concentration, ethylene to PAA molar ratio, and solvent effect were investigated in order to optimize the reaction conditions for enhancing the ethylene conversion and selectivity for EO production. By this approach, the challenges of greenhouse gas production and metal leaching were addressed which were associated with previously reported catalysts.